Los camiones checos - Solano Cornejo, David; Vargas Espinal, Ida Luz (Universidad ESAN. ESAN Ediciones, 1997)
Paico Peru is a subsidiary of an Asian automotive company and is dedicated to the import and sale of cheap cars in Peru. The model that concentrates the highest percentage of sales is the Miso, aimed at socioeconomic levels C and D. Due to the saturation of the main Miso market and new laws that regulate the importation of used cars, an unsatisfied market has been created, So Paico has increased its product portfolio by launching new models aimed at a higher socioeconomic class. The company is currently in a quandary as the board is considering importing a new low-cost truck model that would reinforce the image that Paico sells cheap and low-quality cars, negatively impacting the recent product line.

Paico Perú es una filial de una empresa automotriz asiática y se dedica a la importación y venta de autos económicos en Perú. El modelo que concentra el mayor porcentaje de ventas es el Miso, dirigido a los niveles socioeconómicos C y D. Debido a la saturación del principal mercado de Miso y las nuevas leyes que regulan la importación de autos usados, se ha creado un mercado insatisfecho, por lo que Paico ha incrementado su portafolio de productos lanzando nuevos modelos dirigidos a una clase socioeconómica más alta. Actualmente, la compañía se encuentra en un dilema ya que la junta está considerando importar un nuevo modelo de camión de bajo costo que reforzaría la imagen de que Paico vende autos baratos y de baja calidad, impactando negativamente la reciente línea de productos.
Keywords: Automotive industry; Market segmentation; Industria automotriz; Market positioning; Segmentación del mercado; Posicionamiento del mercado; Market share; Cuota de mercado; https://purl.org/pe-repo/ocde/ford#5.02.04